Clinical Pharmacy Faculty Provision of Direct Patient Care, Challenges, and Opportunities - Korayem, Ghazwa B.; Alqahtani, Lama Ali; Alsulaiman, Sultanah Hisham; Alhammad, Abdullah M.; Badreldin, Hisham A.; Alkhudair, Nora; Al Sulaiman, Khalid; Aljuhani, Ohoud (Frontiers in Medicine, 2023)
Background The quadripartite mission of clinical track faculty members involves research, teaching, services, and direct patient care. However, the extent of faculty involvement in direct patient care remains a challenge. Thus, the study’s objective is to evaluate the effort spent on direct patient care by clinical faculty of pharmacy schools in Saudi Arabia (S.A.) and identify factors that hinder or facilitate providing direct patient care services. Methods This multi-institutional, cross-sectional questionnaire study conducted between July 2021 and March 2022 involved several pharmacy schools’ clinical pharmacy faculty members in S.A. The primary outcome was the percentage of time/effort spent on patient care services and other academic responsibilities. The secondary outcomes were the factors affecting the effort spent on direct patient care and the barriers preventing the provision of clinical services. Results A total of 44 faculty members took the survey. The percentage of effort spent on clinical education was highest at a median (IQR) of 37.5 (30, 50), followed by that spent on patient care [19 (10, 28.75)]. The percentages of effort spent on education and the length of academic experience were negatively associated with efforts spent on direct patient care. The most commonly reported barrier affecting fulfilling patient care duties was the lack of a clear practice policy (68%). Conclusion Although most clinical pharmacy faculty members were involved in direct patient care, half of them devoted only 20% or less of their time to it. An effective effort allocation for clinical faculty duties will require the development of a clinical faculty workload model that sets realistic expectations about the time spent on clinical and non-clinical duties.